Discrete Illumination‐Based Compressed Ultrafast Photography for High‐Fidelity Dynamic Imaging - Jiali Yao; Zihan Guo; Dalong Qi; Shiyu Xu; Wenzhang Lin; Long Cheng; Chengzhi Jin; Yu He; Ning Xu; Zhen Pan; Jiayi Mao; Yunhua Yao; et al. (Advanced Science)
Abstract Compressed ultrafast photography (CUP) can capture irreversible or difficult‐to‐repeat dynamic scenes at the imaging speed of more than one billion frames per second, which is obtained by compressive sensing‐based image reconstruction from a compressed 2D image through the discretization of detector pixels. However, an excessively high data compression ratio in CUP severely degrades the image reconstruction quality, thereby restricting its ability to observe ultrafast dynamic scenes with complex spatial structures. To address this issue, a discrete illumination‐based CUP (DI‐CUP) with high fidelity is reported. In DI‐CUP, the dynamic scenes are loaded into an ultrashort laser pulse train with controllable sub‐pulse number and time interval, thus the data compression ratio, as well as the overlap between adjacent frames, is greatly decreased and flexibly controlled through the discretization of dynamic scenes based on laser pulse train illumination, and high‐fidelity image reconstruction can be realized within the same observation time window. Furthermore, the superior performance of DI‐CUP is verified by observing femtosecond laser‐induced ablation dynamics and plasma channel evolution, which are hardly resolved in the spatial structures using conventional CUP. It is anticipated that DI‐CUP will be widely and dependably used in the real‐time observations of various ultrafast dynamics.